2009
DOI: 10.1007/s11079-009-9130-z
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Cross-Country Index of Trade Specialization

Abstract: International trade, Export specialization, Balassa index, C14, F10, F14,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 22 publications
(21 reference statements)
1
16
0
1
Order By: Relevance
“…Another additive version consists of substituting X JKt for X iKt as the normalization variable, namely total exports in the trade area under consideration (Yu et al 2009). In addition, normalization of the BX ratio by the across-product mean for a given country (Proudman and Redding 1998;Proudman and Redding 2000) or the across-country mean for a given product (Amador et al 2011) has been suggested.…”
Section: Alternative Rca Indexesmentioning
confidence: 99%
“…Another additive version consists of substituting X JKt for X iKt as the normalization variable, namely total exports in the trade area under consideration (Yu et al 2009). In addition, normalization of the BX ratio by the across-product mean for a given country (Proudman and Redding 1998;Proudman and Redding 2000) or the across-country mean for a given product (Amador et al 2011) has been suggested.…”
Section: Alternative Rca Indexesmentioning
confidence: 99%
“…The neglect of the sub-national analysis of exports has been a glaring omission in the existing literature on Portugal, despite evidence of the insurmountable contribution which exports have had towards strengthening the Portuguese economy (Felke and Eide, 2014; Lains, 1994). In Portugal, the attention of policymakers and academics towards export activity has been largely directed to national export performance, often with a firm or sectoral approach (Amador, 2017; Amador et al, 2007a, 2007b; Crespo and Fontoura, 2004). What is little known is what routes industries and firms in different regions have taken in face of the growing phenomenon of internationalisation.…”
Section: Introductionmentioning
confidence: 99%
“…L'analisi del posizionamento competitivo dei Paesi del bacino del Mediterraneo, per i prodotti agroalimentari, avverrà mediante l'accertamento della competitività settoriale basata sull'indice matematico RCA -Revealed Comparative Advantage (vantaggio comparato rivelato). In questo studio l'Indice RCA utilizzato è quello classico proposto originariamente da Balassa (1965) e già ampiamente utilizzato nella letteratura scientifica di settore (Amador et al, 2011;Amighini et al, 2011).…”
Section: Introduzioneunclassified